Trails, Bridges, and Boardwalks - Alan J. Long; Anne Todd-Bockarie; Taylor Stein; Keith Bettcher; Chris Demers (EDIS, 2016)
Trails represent a landowner’s main routes for recreational activities such as walking, sightseeing, horseback riding, and bicycling. They provide access to, and through, forest land and other natural resources. They play an important role in protecting and preserving soil, water, and wild plants and animals. They can be the source of endless hours of enjoyment and relaxation. This 13-page fact sheet will help you plan your trails wisely and construct them carefully so that you and your guests can enjoy them to the fullest. Written by Alan Long, Anne Todd-Bockarie, Taylor Stein, Keith Bettcher, and Chris Demers, and published by the School of Forest Resources and Conservation, August 2016.